1979
DOI: 10.1001/archneur.1979.00500400044005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rehabilitation on Language Skills in Aphasic Patients

Abstract: •The influence of language rehabilitation on specific language skills (speaking, understanding, writing, and reading) was investigated in 281 aphasic patients (162 reeducated and 119 controls) who were subjected to a second examination no less than six months after the first. The relationship of the following factors to improvement was studied: (a) time between onset of aphasia and first examination; (b) type of aphasia; (c) overall severity of aphasia on first examination; (d) presence or absence of rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
1
8

Year Published

1982
1982
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(116 citation statements)
references
References 9 publications
3
104
1
8
Order By: Relevance
“…During that time at least 20 large-scale group treatment studies, enrolling 60 or more patients, and several smaller group studies including at least 10 participants, were published (see, for example, Basso, Capitani, & Vignolo, 1979;Vignolo, 1964;Wertz et al, 1986). Unlike the findings of psychotherapy studies, the results of these group studies largely showed that treatment results in general improvement in language, although, in some cases the treatment effects were not particularly strong or were lacking (Lincoln et al, 1984).…”
Section: A Bit Of Historymentioning
confidence: 99%
“…During that time at least 20 large-scale group treatment studies, enrolling 60 or more patients, and several smaller group studies including at least 10 participants, were published (see, for example, Basso, Capitani, & Vignolo, 1979;Vignolo, 1964;Wertz et al, 1986). Unlike the findings of psychotherapy studies, the results of these group studies largely showed that treatment results in general improvement in language, although, in some cases the treatment effects were not particularly strong or were lacking (Lincoln et al, 1984).…”
Section: A Bit Of Historymentioning
confidence: 99%
“…This resulted in the exclusion of the three large studies of Basso et al (1979), Shewan and Kertesz (1985) and Poeck et al (1989), all indicating significant benefits of treatment. Similarly, single case studies (class IIb) are not considered in the Cochrane reviews.…”
Section: Rehabilitation Of Aphasiamentioning
confidence: 99%
“…Current techniques in speech therapy are least successful with the most severely aphasic patients (Basso, Capitani, & Vignolo, 1979). Despite decades of research into the linguistic mechanisms of aphasia, few new therapeutic modalities are available, especially for the most severely afflicted patients.…”
Section: Introductionmentioning
confidence: 99%